Early Opacifiers In The Glaze Industry Of First Millennium bc Persia: Persepolis And Tepe Rabat. (12th July 2016) - Holakooei, P.; Ahmadi, M.; Volpe, L.; Vaccaro, C.
Abstract : This study characterizes the opacifiers and colouring agents used in the glazed bricks of Persepolis (mid‐first millenniumbc ) and the Mannean site of Tepe Rabat in north‐western Iran (eighth to seventh centuriesbc ). Various analytical studies show that lead antimonate and brizziite (NaSbO3 ) were used as the yellow and white opacifiers in the glazes of Persepolis and Tepe Rabat. Brizziite is shown to be incorporated in the white, green and turquoise glazes, and is also associated with lead antimonate and CaSb2 O6 in some yellow and white opacifiers. The simultaneous formation of these opacifiers in one glaze might have been accidental. A possible connection between the Achaemenid glaze industry and the Mannean glaze production at Tepe Rabat is discussed.